Fully Charged: Characterizing the Data Requirements of Services and Apps to Optimize the Use of Energy - Larracoechea, Jorge Andrés; Ilarri, Sergio; Roose, Philippe (Jornada de Jóvenes Investigadores del I3A, 2020)
Energy is consumed in devices in a different manner according to their available limited resources (such as battery) in an attempt to fulfill tasks imposed by the services’ processing and data demands. This has led ICT researchers to find interest in strategies for mitigating high energy consumptions when processing and transferring data. For example, efforts on delivering efficient software code that preserves energy by being architecturally efficient and conscious about resource usage have been done in the past, but we consider that other approaches could be implemented in order to further increase energy savings.  We present an introduction to our future work that aims at analyzing and categorizing a wide range of situations and example applications that may have an impact on the most suitable decisions to be taken regarding the needs of the service/application and the expected energy consumption.